2017
DOI: 10.1016/j.apsusc.2017.01.305
|View full text |Cite
|
Sign up to set email alerts
|

Anisotropic Raman scattering and mobility in monolayer 1T d -ReS 2 controlled by strain engineering

Abstract: Regulation of electronic structure and mobility cut-on rate in two-dimensional transition metal dichalcogenides (TMDs) has attracted much attention because of its potential in electronic device design. The anisotropic Raman scattering and mobility cut-on rate of monolayer unique distorted-1T(1Td) ReS2 with external strain are determined theoretically based on the density function theory. The angle-dependent Raman spectrum of Ag-like, Eg-like and Cp models are used to discriminate and analysis structural anisot… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 33 publications
0
20
0
Order By: Relevance
“…Recently, the electrical transport properties of n-type field effect transistor devices have been reported to be strongly anisotropic [8,35,36], and the conduction band electron mobility was found to be about three times larger along the rhenium chains compared to the direction perpendicular to them [8]. In the Supplemental Material, Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, the electrical transport properties of n-type field effect transistor devices have been reported to be strongly anisotropic [8,35,36], and the conduction band electron mobility was found to be about three times larger along the rhenium chains compared to the direction perpendicular to them [8]. In the Supplemental Material, Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Previous reports have suggested that the E g -3 mode involves out-of-plane vibrations of the S atoms along with in-plane vibrations of Re atoms and that the A 1g -4 mode results from the out-of-plane vibrations of S atoms. 10,15 As the distortion of Re4 units occurs at a much lower pressure (6.8 GPa), as discussed above, the splitting phenomena at 15.4 GPa should be attributed to the changes of force constants of S atoms. Previous theoretical calculations have indicated that ambient ReS 2 is randomly stacked, because shifting one ReS 2 monolayer over another does not lead to any significant change in total energy owing to its weak interlayer coupling.…”
mentioning
confidence: 83%
“…For ReS 2 materials, there are 36 vibrational modes which can be written as Γ Raman = 18­(A g + A u ) being the cause of 12 atoms in the primitive cell . Getting rid of 15 infrared-active modes and 3 zero-frequency modes, the 18 Raman-active modes which belong to the symmetric A g modes can be detected. , All the Raman-active modes of the ReS 2 films are shown in Figure . These Raman spectra of the ReS 2 films display more complex peaks than those of conventional TMDs such as MoS 2 and WS 2 .…”
Section: Results and Discussionmentioning
confidence: 99%